2003
DOI: 10.1038/sj.ejhg.5200968
|View full text |Cite
|
Sign up to set email alerts
|

Influence of missense mutation and silent mutation of LHβ-subunit gene in Japanese patients with ovulatory disorders

Abstract: The frequency of variant LHb containing two point mutations (T 986 -C and T 1008 -C) and its relationship to reproductive disorders differ widely between ethnic groups. In a Japanese population, variant luteinizing hormone (LH) correlates with ovulatory disorders. Here we examined the relationship between two missense mutations and five silent mutations (C 894 -T, G 1018 -C, C 1036 -A, C 1098 -T and C 1423 -T) in the LHb gene, and ovulatory disorders. We studied 43 patients with ovulatory disorders, 79 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
0
12
0
2
Order By: Relevance
“…Haploview and Pypop softwares were used to estimate LD and generate haplotype frequencies. The nucleotide positions mentioned for individual SNP is according to Takahashi et al (2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Haploview and Pypop softwares were used to estimate LD and generate haplotype frequencies. The nucleotide positions mentioned for individual SNP is according to Takahashi et al (2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, the relation between a mutant LH gene and female infertility has not yet been established clearly. While some investigators have reported the clinical significance of the variant LH in Japanese patients with reproductive disorders including infertility and/or menstrual disorders (Furui et al, 1994;Huhtaniemi et al, 1999;Takahashi et al, 2003), Finnish women carrying the variant LH (detected in 28% of the population) were reported to be fertile (Haavisto et al, 1995;Nilsson et al, 1997). Thus, evidence concerning the clinical significance of the variant LH with respect to reproductive disorders has been contradictory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been speculative suggestions that the allelic variant Arg8/Thr15 of the LH β-subunit gene may correlate with the changes in the pituitary-gonadal function 13,18,19,22 and menstrual disorders. 14,26 Our study indicates that the allelic variant Arg8/Thr15 of the LH β-subunit gene is a polymorphism that is also commonly found in the Brazilian population.…”
Section: Discussionmentioning
confidence: 99%
“…6,[15][16][17] These polymorphisms are in complete linkage disequilibrium, and they have been found in both infertile patients and reproductively healthy subjects of several populations, with a relatively high frequency (41.9% to 53.5%) in Finnish Lapp populations and in Australian aborigines. [13][14][18][19][20][21][22][23][24][25][26][27] Latin-American populations have not been studied to date.…”
mentioning
confidence: 99%